Creativity and humor - Luria, Sarah R.; Baer, John, 1948-; Kaufman, James C. (Explorations in creativity research., 2019)
"Creativity and Humor provides an overview of the intersection of how humor influences creativity and how creativity can affect humor. The book's chapters speak to the wide reach of creativity and humor with different topics, such as play, culture, work, education, therapy, and social justice covered. As creativity and humor are individual traits and abilities that have each been studied in psychology, this book presents the latest information. Explains how, and why, humor enhances creativity. Explores the thought processes behind producing humor and creativity. Examines how childhood play is the basis for both creativity and humor. Discusses cross-cultural differences in humor and creativity. Reviews creativity and humor in politics, teaching and relationships."--Provided by publisher.